Pengaruh Perputaran Modal Kerja dan Perputaran Persediaan Terhadap Profitabilitas - Putri, Delia Anggraeni; Ritonga, Ferdiansyah (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2024)
This observation will analyze consumer-facing company listed on the Indonesian Stock Exchange and their profitability from 2019 to 2023. It will look at how these companies handle working capital and inventory turnover. A quantitative approach is used in the study using descriptive statistics. The results of this investigation were based on information retrieved from the IDX database. Out of 299 organizations that supplied observation data, we selected 68 using a random selection approach. This study was analyzed using the tools of eviews version 12. A capital turnover variable shows that working capital turnover is positively correlated with profitability. Several indicators of inventory turnover point to a positive, although negligible, impact of turnover on profitability. This finding suggests that the result of the interaction of the independent factors of the dependent variable. As a result, this study suggests tat companies should remain consistent in managing working capital and evaluating inventory control to achieve high profitability.